2021
DOI: 10.1038/s41598-021-99866-w
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of various gargle formulations and salt water against SARS-CoV-2

Abstract: The COVID-19 is difficult to contain due to its high transmissibility rate and a long incubation period of 5 to 14 days. Moreover, more than half of the infected patients were young and asymptomatic. Virus transmission through asymptomatic patients is a major challenge to disease containment. Due to limited treatment options, preventive measures play major role in controlling the disease spread. Gargling with antiseptic formulation may have potential role in eliminating the virus in the throat. Four commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 34 publications
0
20
0
1
Order By: Relevance
“…These effects were confirmed by electron microscopy. In addition, analogous experiments using CPC diluted in filtered saliva showed similar antiviral results [ 40 ]. Future experiments will discern if the addition of compounds like CPC to mouthwashes is a valid strategy to fight against other enveloped virus, such as other coronaviruses [ 7 ].…”
Section: Discussionmentioning
confidence: 64%
“…These effects were confirmed by electron microscopy. In addition, analogous experiments using CPC diluted in filtered saliva showed similar antiviral results [ 40 ]. Future experiments will discern if the addition of compounds like CPC to mouthwashes is a valid strategy to fight against other enveloped virus, such as other coronaviruses [ 7 ].…”
Section: Discussionmentioning
confidence: 64%
“…Coughing once or having a five-minute conversation can produce up to 3000 droplets of saliva, whereas a sneeze can produce up to 40,000 droplets [ 18 ]. It has recently been shown that mouthwashes can rapidly inactivate SARS-CoV-2 through in vitro [ 2 , 16 , 19 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and in vivo studies [ 3 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Subsequently, there have been extensive discussions regarding the utilization of mouth rinses to possibly complement current prevention measures such as facemasks, hand disinfection, and social distancing in order to reduce the global spread of SARS-CoV-2 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Koch-Heier et al, evaluated two rinses—ViruProX® (0.05% CPC and 1.5% H 2 O 2 ) and BacterX® (0.1% CHX, 0.05% CPC, and 0.005% fluoride)—and their results showed that 0.1% CHX and 1.5% H 2 O 2 present in the rinses did not exhibit a reduction in viral load, although 0.05% CPC present in both rinses was responsible for the virucidal effect against SARS-CoV-2, which significantly reduced the viral load [ 24 ] ( Table 1 ). Tiong et al found that CPC was able to decrease around 99.99% of the concentration of SARS-CoV-2 after 30 s of exposure, exhibiting a slightly higher virucidal activity than CHX [ 26 ] ( Table 1 ).…”
Section: Types Of Oral Antiseptics Against Sars-cov-2mentioning
confidence: 99%
“…Consistently, CHG was also ineffective in the oral cavity [ 35 ]. Studies in which CHG had been found to be effective [ 36 ] were apparently based on incomplete neutralization of CHG adsorbed to virus and only simulated efficacy. Results differ for stabilized hypochlorite [ 32 ].…”
Section: State Of Knowledge On the Virucidal Efficacy Of Mouthrinse/g...mentioning
confidence: 99%
“…Gargling with hypertonic saline (2%–3%) 3 times/d significantly shortened the duration of illness from viral influenza, with the reduction in viral shedding reducing the incidence of illness by 35%, even among people living in the same household. Since saline is not virucidal in vitro [ 36 ], hypochlorite is probably formed intracellularly due to the increased chlorite availability; it is also possible that viral adherence is reduced.…”
Section: State Of Knowledge On the Virucidal Efficacy Of Mouthrinse/g...mentioning
confidence: 99%